2011
DOI: 10.1111/j.1468-3083.2011.04372.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased gene expression of Toll‐like receptor 4 on peripheral blood mononuclear cells in patients with psoriasis

Abstract: Differential TLR4 ⁄ 2 gene expressions on psoriatic peripheral blood mononuclear cells and correlations with regulatory and ⁄ or proinflammatory cytokines and ⁄ or damage-associated molecular pattern molecule S100A9 emphasize innate immune response role in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 56 publications
4
40
0
4
Order By: Relevance
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 80%
“…The results support the involvement of innate immune response elements in the pathophysiology of psoriasis, in line with previous studies (12,17,(22)(23)(24)26,27,(32)(33)(34)(35)(36), although some previous studies have reported conflicting results regarding TLR-9 expression in psoriasis (22,34). The activation of IL-33, TLR-2 and TLR-9 in psoriatic plaques may be important since such activation has been previously associated with the activation of NF-κB (12,23,37).…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, Toll‐like receptors (TLRs) of epidermal cells are transmembrane proteins, with the extracellular portions or the intracellular portions conjugated to corresponding ligands, capable of initiating innate immune responses and influencing subsequent adaptive immune responses 31, 32. Evidence supported that TLR4 in immune response has been revealed in the pathogenesis of psoriasis 33, and increased gene expression of TLR4 on peripheral blood mononuclear cells in patients with psoriasis was revealed 34. In addition, although the negative correlation of TLR4 with miR181‐b has been revealed in a previous study in acute myeloid leukaemia 35, whether such a correlation was still existed in on psoriasis pathogenesis remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These mice had exaggerated inflammatory response when challenged by exogenous stimuli such as abrasion (Koebner phenomenon), potentiated inflammation by acting directly as a chemoattractant for leukocytes [13]. Differential Toll-like receptor (TLR4/2) genes expression on psoriatic peripheral blood mononuclear cells were correlated with regulatory proinflammatory cytokines and damage-associated molecule (S100A9) that emphasize innate immune response role in psoriasis [14].…”
Section: Discussionmentioning
confidence: 97%